Prospective study to optimize the health of patients with TIAS (transient ischemic attack) and stroke admitted to the Hamad General Hospital. Issue 28 (10th July 2020) - Imam, Yahia Z.; Mohamed, Mouhand F.H.; Abdelmoneim, Mohamed S.; Santos, Mark; Alkhawad, Nima; Salam, Abdul; Amir, Numan; Saqqur, Maher; Muhammad, Ahmad; Elsoutohy, Ahmed; Kamran, Saadat; Akhtar, Naveed; et al.
Abstract: Introduction: Recurrent ischemic strokes (IS) make up to one-third of all strokes. Nine out of 10 strokes are due to modifiable risk factors. Thus, it seems that standard management strategies of modifiable risk factors are yet to improve. Hence, we planned a randomized controlled trial assessing nurses or pharmacists-led aggressive control of comorbidities and their prognostic impact on IS and transient ischemic attacks (TIA). Methods/design: Prospective study to optimize the health of patients with TIAs and stroke admitted to the Hamad General Hospital (PROMOTE HEALTH) is an assessor-blinded, open-label, randomized, two-arm, controlled trial. Eligible patients have IS or TIA, and an additional modifiable risk factor (Hypertension or dyslipidemia) attending the stroke ward or clinic at the Weill Cornell-affiliated Hamad General Hospital. Stroke specialists will offer the control group the currently practiced best risk factor management strategies. Whereas, in the intervention arm, with the assistance of a nurse and a pharmacist, we will make aggressive attempts to meet targets of defined risk factors. The primary outcomes are the mean difference in blood pressure (BP) and low-density lipoprotein. Whereas myocardial infarction, recurrent stroke events, and mortality serve as the study's secondary outcomes. We require 200 patients per study arm to achieve a power of 80% and an alpha level of <0.05. The Medical Research Center and the Institutional Review Board have approved the study, and it was prospectively registered in a trial registry. Discussion: A significant proportion of strokes are due to modifiable preventable risk factors. Despite having the right preventive strategies aimed at mitigating these risk factors, a sizeable proportion of strokes are due to recurring events. This prompted the medical community to evaluate aggressive means of addressing these risk factors. The nurse or pharmacist-led management of comorbidities has been proven to be of value in the management of diabetes and hypertension. It will be of value to demonstrate the effectiveness of utilizing this additional task force in aggressively managing IS or TIA patients with an overarching goal of improving their prognosis. If our intervention proves to be efficacious, this would have a substantial impact on the current stroke practices and guidelines. Additionally, it will invite further research in the area. Clinical trial registration: Clinicaltrials.gov NCT02868723, last updated on September 2018